Pengaruh Motivasi Belajar terhadap Hasil Pembelajaran Baca Tulis Al-Qur’an: Analisis pada Siswa SMP Al-Hassan Balikpapan - Ghoitsur rijal; Iskandar Yusuf (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to determine the influence of learning motivation on the learning outcomes of Qur’an Reading and Writing (BTQ) among students at SMP Al-Hassan Balikpapan. The research employed a quantitative method with data collected through questionnaires distributed to 31 students from grades VII, VIII, and IX. The research instruments were tested for validity and reliability, showing that all items were declared valid and reliable. A normality test indicated that the data were normally distributed, allowing for the use of parametric statistical analysis. The results of the simple linear regression analysis showed that the t-count value of 2.065 was greater than the t-table value of 2.045. However, the significance value (0.049) was slightly above the critical threshold of 0.05, indicating that the effect of learning motivation on BTQ learning outcomes is weak or not strongly significant. The R Square value of 0.136 indicates that learning motivation contributes only 13.6% to BTQ learning outcomes, while the remaining 86.4% is influenced by other factors. It can be concluded that learning motivation has an effect on BTQ learning outcomes, but the influence remains relatively low.